Environmental Policy à la Carte: Letting Firms Choose their Regulation - Frank C. Krysiak; Iris Maria Oberauner (University of Basel, Center of Business and Economics (WWZ), 2008)
Environmental policy often has to be devised under informational constraints, like uncertainty and asymmetric information. We consider an environmental policy that aims at reducing the welfare losses caused by asymmetric information while being sufficiently simple for implementation. In this policy, firms can choose between being regulated with an emission tax or a permit market. This serves as a screening device; the firms reveal private information by choosing an instrument. We show that such a menu of policy options improves upon conventional environmental policy. Furthermore, the optimal policy is simple and thus easily implementable. The approach is also theoretically interesting, because the simultaneous use of price- and quantity-based instruments induces an asymmetry into the pricesversus- quantities decision compared to Weitzman's criterion. Especially, there can be an optimal pooling equilibrium where all firms choose the tax, but it is never optimal that all firms participate in permit trading.
Keywords: Q58; D82; H23; D81; Q54; 330; Environmental Policy; Asymmetric Information; Screening; Uncertainty; Prices-versus-Quantities; Umweltpolitik; Asymmetrische Information; Entscheidung unter Unsicherheit; Technologiewahl; Regulierung; Prinzipal-Agent-Theorie; Theorie